Pengaruh Persentase Perekat terhadap Pembuatan Biobriket dari Pelepah Sawit dan Tempurung Kelapa - Nina Veronika (Jurnal Sains dan Ilmu Terapan, 2024)
Energy demand in the world, especially Indonesia, continues to increase, while the supply of fossil fuels is decreasing. Alternative energy can be created through outputs from agricultural products, both in the form of cultivated plants, as well as those sourced from agricultural residues (biomass) which do have a fairly high sustainability value. Palm fronds are one of the biomass wastes produced from the palm oil industry, containing cellulose and other substances that can be utilised as a source of energy, by processing them into briquettes. Coconut shells also contain cellulose and substances that can be utilised as one of the energy sources that can be processed into briquettes. This study aims to determine the process of making briquettes, knowing the effect of variations in the percentage of adhesive on the briquettes produced, knowing whether the products produced are in accordance with SNI. The research stage consists of: preparation of raw materials, charring, mixing adhesives, printing, and drying briquettes. Variations in the percentage of adhesive used are 15%, 20%, 25%.